Some Structural Properties of Fully UP-semigroups (European Journal of Pure and Applied Mathematics, 2019)
This paper investigates a new class of algebra related to UP-algebras and semigroups called fully UP-semigroups (or $f$-UP-semigroups). It establishes some structural properties of $f$-UP-semigroups. It also introduces and examines $f$-UP-fields, $f$-UP-domains, $f$-UP-ideals, and quotient $f$-UP-semigroups. Moreover, it investigates the relationship betweenÂ  an $f$-UP-field and an $f$-UP-domain.